Fundamentals of Mathematics and Statistics and Arts and Science (Revised Syllabus) - Deshpande Rekha, Saptarshi R., Desai N. sargar G.K. (Nirali Prakashan, Pune, 2006)
Stats/Maths
ENGLISH
Keywords: Fundamentals of Mathematics and Statistics and Arts and Science (Revised Syllabus); Stats/Maths; Stats/Maths